STUDENTS’ PERCEPTION TOWARD HELLO ENGLISH APPLICATION AS MEDIA IN LEARNING VOCABULARY AT SEVENTH GRADE OF SMP KRISTEN IMMANUEL BATAM - Reminiscere Gultom; Juwita Boneka Sinaga (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
The objective of this study is to find out the students’ perception toward Hello English application as media in learning vocabulary at SMP Kristen Immanuel Batam. This study utilized a qualitative descriptive method. The researcher used an instrument questionnaire and interview. The instrument questionnaire use three factors of influence perception are Perceiver, Target, and Situation. There are thirteen indicators in the instrument questionnaire namely: Attitude, Motive, Interest, Experience, Expectation, Novelty, Motion, Background, Proximity, Similarity, Time, Work Setting, and Social Setting. But interview instrument only use one factor of perception based on the individual concerned (perceiver) with five indicators: Attitude, Motive, Interest, Experience, and Expectation. In analyzing the data from a questionnaire, the researcher did some steps, they were scoring the students, classifying the score of the students using likert scale, the classification of the students’ scores, and the percentage formula of the students. Then data from the interview were used to clarify and strengthen the data from the questionnaire. The finding of this research showed that Hello English application has many benefit for students because Hello English application is not only to memorize vocabulary but also some students can learn about writing the text vocabulary, answering the question, speaking the text, and building sentences on Hello English application. Therefore it could be assumed that all students perceived positively toward Hello English application as media for learning vocabulary.